1998
DOI: 10.1029/98jd01857
|View full text |Cite
|
Sign up to set email alerts
|

Isoprene emissions from boreal wetlands in Scandinavia

Abstract: Abstract. Seasonal emissions of isoprene and other light hydrocarbons were measured from both an elevated dry site (hummock) and low wet site (flark) on a Sphagnum fen in Sweden, and diurnal emissions were measured from a wet site on a Sphagnum fen in Finland. Both fens are in the southern boreal zone. Samples were taken from a Teflon chamber with stainless steel canisters, and analysis was done by gas chromatography with flame ionization detection. Isoprene clearly dominated the flux of light hydrocarbons, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 13 publications
7
49
2
Order By: Relevance
“…Linear fit gives the standard emission potential of 680 µg m −2 h −1 with R 2 of 0.70. This agrees well with the results of Janson and De Serves (1998), who reported average standard emission potential of 708 µg m −2 h −1 from flarks of boreal wetlands.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Linear fit gives the standard emission potential of 680 µg m −2 h −1 with R 2 of 0.70. This agrees well with the results of Janson and De Serves (1998), who reported average standard emission potential of 708 µg m −2 h −1 from flarks of boreal wetlands.…”
Section: Resultssupporting
confidence: 83%
“…The isoprene fluxes from the Siikaneva fen are in same range with the emissions measured from a boreal fen by Janson and De Serves (1998) and Janson et al (1999). The daytime isoprene emission rates from Siikaneva were in the same range than the monoterpene emissions from boreal forests (Rinne et al, 1999(Rinne et al, , 2000a(Rinne et al, , 2000bSpanke et al, 2001).…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…around the Baltic Sea near Finland) where constraints on isoprene emissions could be improved by using measurement data that is available in the literature (e.g. Jansen and De Serves, 1998;Lindfors and Laurila, 2000). Recently comparisons of European isoprene mixing ratios calculated online in a CTM with MEGAN against similar EMEP data for 2006 have also shown that there is a wide variability in agreement between different EMEP sites even when including yearly specific meteorological variability during the derivation of emission fluxes (Zare et al, 2012).…”
Section: Isoprenementioning
confidence: 99%